Hybrid Radio over Fiber with Radio over Free Space Optic for 5G Fronthaul Network Implementation in Urban Areas - Nabila Syadzwina Effendi; Yus Natali; Catur Apriono (Jurnal Rekayasa Elektrika, 2023)
Optical fiber can meet the demand for fronthaul on 5G networks that offer high bandwidth, large capacity, high data rate and is free from electromagnetic interference. However, deploying infrastructure faces issues like permits and high costs. Hybrid Radio over Fiber (RoF) technology with Radio over Free Space Optic (RoFSO) can be a solution in urban areas, where the installation requires high costs. This research investigates a hybrid RoF-RoFSO scheme at a frequency of mmWave 26 GHz by considering atmospheric attenuation values arising from meteorological effects, such as rain, smog, and dust,  using Optisystem. This research considers QPSK, 16-QAM, and 64-QAM modulation schemes, distance variations on the FSO and the meteorological data from the Indonesian Meteorology, Climatology and Geophysics Agency (BMKG) from March 2022 to May 2022. The results show that attenuation due to high rainfall is the main cause of signal quality degradation and limits the transmission distance on the FSO link. The maximum distance is 600 m using the QPSK and 16-QAM modulation schemes, while for the 64-QAM modulation scheme, the maximum transmission distance is 500 m. Meanwhile, damping values caused by foggy and dusty conditions can reach distances of up to 1000 m for the three modulation schemes.